Maritime Students’ Financial Knowledge, Attitude, and Behavior - Apao, Ariel A.; Cayanpat, Rean Angelie B.; Edullantes Jr., Yolando P.; Cabañero, Kein Eduard S.; Hechanova, John Mark T.; Candia, Hakim G. (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
Money plays an important role in daily decision-making, and in today’s challenging financial world, it is essential for young people to become financially literate early. This study explored how financial knowledge and financial attitude relate to the financial behavior of maritime students. A descriptive-correlational research design was used, involving 100 randomly selected maritime students from a private higher education institution in Ozamiz City. Data were gathered using standardized questionnaires on financial knowledge, attitude, and behavior. The data were analyzed using mean, standard deviation, and Pearson correlation. Findings showed that the maritime students had very high levels of financial knowledge, attitude, and behavior. However, the results revealed no significant relationship between financial knowledge and behavior, nor between financial attitude and behavior. Although students may be knowledgeable and have positive attitudes toward finance, these do not necessarily translate into consistent financial behavior. Therefore, financial education may not only focus on increasing knowledge and attitude but also on helping students apply these in real-life situations. In this vein, future studies may consider other factors that may influence financial behavior, such as peer influence, family background, or financial stress. Qualitative studies may also offer deeper insights into students’ financial experiences. Students are encouraged to practice simple financial habits like keeping a spending log, setting saving goals, and identifying needs versus wants.